2002
DOI: 10.1093/aje/kwf150
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Reduction, Smoking Cessation, and Mortality: A 16-year Follow-up of 19,732 Men and Women from the Copenhagen Centre for Prospective Population Studies

Abstract: The authors investigated the association between changes in smoking habits and mortality by pooling data from three large cohort studies conducted in Copenhagen, Denmark. The study included a total of 19,732 persons who had been examined between 1967 and 1988, with reexaminations at 5- to 10-year intervals and a mean follow-up of 15.5 years. Date of death and cause of death were obtained by record linkage with nationwide registers. By means of Cox proportional hazards models, heavy smokers (>or=15 cigarettes/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
3
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(119 citation statements)
references
References 35 publications
6
102
3
8
Order By: Relevance
“…[98][99][100][101][102][103] Similarly, recent findings from the D:A:D study demonstrated a decreasing risk in CVD with increasing years of having stopped smoking. 31 Nevertheless, preventing smoking in HIV-positive patients is challenging.…”
Section: Preventionmentioning
confidence: 99%
“…[98][99][100][101][102][103] Similarly, recent findings from the D:A:D study demonstrated a decreasing risk in CVD with increasing years of having stopped smoking. 31 Nevertheless, preventing smoking in HIV-positive patients is challenging.…”
Section: Preventionmentioning
confidence: 99%
“…Luoto et al (2000) reported that after 18 years of follow-up, occasional smokers had an increased RR (1.6) for total mortality and for CVD mortality (1.5) and that CVD risk was comparable for light and heavier smokers. Godtfredsen, Holst, Prescott, Vestbo, and Osler (2002) reported that smokers who reduced their consumption by 50% had no reduction in CVD, respiratory diseases, tobacco-related cancers, or all-cause mortality compared with continuing heavy smokers.…”
Section: Is Cigarette Consumption a Valid Measure Of Disease Risk?mentioning
confidence: 99%
“…25 In a study of 19,732 patients, smoking reduction yielded no decrease in mortality from tobacco-related disease. 26 The only known way to reduce cancer risk in smokers is complete cessation, which results in a 35% lower risk of death due to tobacco-related illness and a 64% reduced risk of tobacco-related cancer. [27][28][29] The only benefit to the smoker in reducing the number of cigarettes smoked may be greater ease in quitting.…”
Section: Introductionmentioning
confidence: 99%